WORLD POPULATION COMPOSITION, ITS CHANGES, AND PROSPECTS - Gulomov, Saidakhror Saidakhmedovich; Pardaev, Mamaynus Karshibaevich; Pardaev, Dilshod Subonkulovich (THE INNOVATION ECONOMY, 2026)
This article examines the composition of the world population, its changes, and prospects, including the rate of change in the world population from 1960 to 2025 and projected figures for 2050, the state of the 20 largest countries by population in 2025, and projected figures for 2100. The wealth of the 15 richest countries at the beginning of 2026 is also analyzed. The ethnic composition of the population is also calculated and analyzed, in particular, the ethnic composition of the permanent population residing in Uzbekistan and its share of the total population.